Study on the spatiotemporal differentiation and influencing factors of regional industrial carbon emission efficiency under the background of green development—a case study of Sichuan Province - Yang, Runjia; Feng, Tingting; Zhao, Shuang (Frontiers in Environmental Science, 2025)
Industrial carbon emission reduction is not only the need to cope with climate change and environmental pollution, but also an important way to achieve sustainable economic development. This paper first constructs an evaluation system of urban green development index from four dimensions: economy, society, resources and environment. Then, the undesirable super-efficiency SBM model is used to measure the static industrial carbon emission efficiency, and the spatiotemporal characteristics of the dynamic industrial carbon emission efficiency are analyzed by combining the Malmquist index. Finally, the urban green development index was incorporated into the Tobit regression model, and the impact of energy intensity, urban structure and other factors on industrial carbon emission efficiency was considered. This paper cited 18 cities in Sichuan Province from 2015 to 2022 as an example for analysis. The results show that the overall green development level of Sichuan from 2015 to 2022 shows a downward trend, and there is great room for improvement in the level of green development. The average industrial carbon emission efficiency in Sichuan is 0.740, and the difference in industrial carbon emission efficiency is mainly due to the difference in pure technical efficiency. From 2015 to 2022, Sichuan’s industrial carbon emission efficiency showed a trend of first stable and then decreasing. There is a significant positive correlation between the level of green development and the efficiency of industrial carbon emissions. Altogether, the industrial carbon emission efficiency model established in this paper is of vital magnitude to the low-carbon development of regional industry.